Evaluation of Human Kidney Injury Molecule 1 (hKIM-1) Expression in Tumors From Various Organs by Messenger RNA In Situ Hybridization. Issue 2 (20th February 2021) - Sarami, Iman; Shi, Jianhui; Lin, Benjamin; Liu, Haiyan; Monroe, Robert; Lin, Fan
Abstract: Objectives: Human kidney injury molecule 1 (hKIM-1) is a sensitive and specific marker for detection of clear cell renal cell carcinoma (CRCC), papillary renal cell carcinoma (PRCC), and ovarian clear cell carcinoma (OCCC). Its use was limited to a few surgical pathology laboratories because this specific antibody to hKIM-1 was not commercially available. We investigated the diagnostic utility of RNA in situ hybridization/RNAscope in the detection of hKIM-1 in tumors from various organs. Methods: RNAscope for hKIM-1 was performed on 1, 252 cases on tissue microarray sections, including CRCC (n = 185), PRCC (n = 59), chromophobe renal cell carcinoma (n = 18), oncocytoma (n = 12), OCCC (n = 27), and metastatic CRCC (n = 46). Results: Fifty-nine (100%) of 59 PRCCs, 94 (95%) of 99 low-grade CRCCs, 83 (96%) of 86 high-grade CRCCs, and 24 (89%) of 27 OCCCs, and 44 (96%) of 46 metastatic CRCCs were positive for hKIM-1. In contrast, hKIM-1 expression was not seen in normal renal tubules or in most nonrenal tumors. Low-level expression could be seen in a small percentage of urothelial, hepatocellular, and colon carcinomas. Conclusions: hKIM-1 is a sensitive and relatively specific marker (1) for diagnosing PRCC, CRCC, and OCCC when working on a tumor of unknown origin and (2) for differentiating CRCC from chromophobe renal cell carcinoma and oncocytoma.